(untitled) (Eurasian Scientific Herald, 2024)
Adhesive bridges (AMP) are a relatively new and promising direction in dentistry and orthopedics, which allows solving the problem of restoring the continuity of the dentition with minimal invasion into the hard tissues of the teeth.